2010
DOI: 10.1186/1471-2474-11-75
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopy vs. MRI for a detailed assessment of cartilage disease in osteoarthritis: diagnostic value of MRI in clinical practice

Abstract: BackgroundIn patients with osteoarthritis, a detailed assessment of degenerative cartilage disease is important to recommend adequate treatment. Using a representative sample of patients, this study investigated whether MRI is reliable for a detailed cartilage assessment in patients with osteoarthritis of the knee.MethodsIn a cross sectional-study as a part of a retrospective case-control study, 36 patients (mean age 53.1 years) with clinically relevant osteoarthritis received standardized MRI (sag. T1-TSE, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
40
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 44 publications
5
40
1
3
Order By: Relevance
“…MRI has been shown to have diagnostic value in delineating articular and soft tissue injury, with sensitivities and positive predictive values near 90%. 29 MRI in our study confirmed osteochondral injury in almost half of our patients (44%) despite plain radiograph interpretation as negative for fracture. MRI is strongly recommended after APD for accurate diagnosis and guiding treatment.…”
Section: Discussionsupporting
confidence: 50%
“…MRI has been shown to have diagnostic value in delineating articular and soft tissue injury, with sensitivities and positive predictive values near 90%. 29 MRI in our study confirmed osteochondral injury in almost half of our patients (44%) despite plain radiograph interpretation as negative for fracture. MRI is strongly recommended after APD for accurate diagnosis and guiding treatment.…”
Section: Discussionsupporting
confidence: 50%
“…Although MRI was not used in our study, both standing and recumbent magnets can be used for longitudinal examination of this region in the horse and should be considered for future studies. However, we were able to use arthroscopic imaging which is often used as the gold standard for identification and staging of articular cartilage disease 47, 48 since it allows better assessment of the cartilage surface and synovial membrane than MRI, including characterization of the location and severity of lesions 49, 50 . The large size of the animals used in this study was advantageous for arthroscopic and histological data collection, as well as for synovial fluid collection (average 4.3 mL/MCP joint/sample).…”
Section: Discussionmentioning
confidence: 99%
“…19). The high number of false-negative findings is predominantly secondary to suboptimal spatial resolution and the resulting difficulty in identifying lowgrade, partial-thickness lesions [58,59]. The in-plane spatial resolution needed to detect superficial degenerating cartilage is 0.3 9 0.3 mm [60].…”
Section: Cartilagementioning
confidence: 99%